Numérique et autonomisation des élèves : quelle formation initiale des enseignants ? - Ghislaine Gueudet; Sophie Joffredo-Le Brun; Antoine Le Bouil; Carole Le Hénaff; Gwenaëlle Riou-Azou; Sabrina Srey (Recherches en Éducation)
Using digital technology in class to support the development of students' autonomy is recommended by the educational authorities; nevertheless it is a complex objective for teachers. In this article we investigate how an initial training based on collective documentation work for designing classroom scenarios can contribute to achieving this objective for trainee teachers. We present three case studies, in English (as a foreign language), mathematics and physics. We analyse the potential of trainee-designed lesson plans in terms of digital uses and autonomous learning, and seek to identify emerging operational invariants by drawing on the scenarios and their presentation by the trainees. The comparison of the three disciplines shows common features and disciplinary specificities.